The effects of leniency on illegal transactions: How (not) to fight corruption - Paolo Buccirossi; Giancarlo Spagnolo (Stockholm School of Economics, The Economic Research Institute (EFI), 2001)
We study the consequences of 'leniency' - reduced legal sanctions for wrongdoers who spontaneously self-report to law enforcers - on corruption, drug dealing, and other forms of sequential, bilateral, illegal trade. We find that when not properly designed, leniency may be highly counterproductive. In reality leniency is typically moderate, in the sense of only reducing, or at best cancelling the sanctions for the self-reporting party. Moderate leniency may greatly facilitate the enforcement of long-term illegal trade relations, and may even provide an effective enforcement mechanism for occasional (one-shot) illegal transactions, which would not be enforceable otherwise.
Keywords: K00; K21; K42; 330; Law enforcement; Self-reporting; Corruption; Crime; Illegal trade; Drug dealing; Korruption; Strafverfahren; Wirtschaftskriminalität; Theorie